Optimization of external spray negative-pressure mist-curtain dust suppression devices for roadheaders based on a multi-factor orthogonal experiment. (1st December 2020) - Peng, Huitian; Nie, Wen; Liu, Zhiqiang; Xiu, Zihao; Yang, Shibo; Xu, Changwei; Ma, Qingxin; Guo, Cheng
Abstract: To improve the dust removal efficiency of external spray negative-pressure mist-curtain dust suppression devices, a multi-factor orthogonal experiment was designed and a numerical simulation was carried out for these types of devices. According to changes in the measurement factor values in the simulation results, the main factors affecting the negative-pressure suction effect of the device were obtained through analysis and ranked in the order: Nozzle installation position > Angle of the conical cover > Length of the conical cover; the significant analysis results were FA  < FB  < F0.05  < Fc  = 59.49 < F0.01 . The F-test showed that the nozzle installation position had the most significant impact on the measuring factor, while the length of the conical cover A, and the angle of the conical cover B, had less impact on the measuring factor. According to the principles of high efficiency and low consumption, the length and angle of the conical cover were determined to be 100 mm and 15.6°, respectively, and the installation position of the nozzle was determined to be 10 mm. Once the structure of the device had been improved, the original and the improved negative-pressure mist-curtain dust suppression devices were compared in a field application. The removal efficiency of the improved negative-pressure jet dust of the device was increased by 4.99%, 4.83%, 5.12%, and 3.73% at the driver's place, the reversed loader, and 50 and 100 m from the heading face, respectively. Graphical abstract: Image 1 Highlights: The negative-pressure mist-curtain dust suppression device was improved. A multi-factor orthogonal experiment was designed. The effects of different factors and levels on the effect of suction were studied. The effect of the water mist piston mechanism on suction volume was studied. The negative-pressure jet dust removal efficiency of the device was improved.